Aplicación web para la asociación de artesanos de la parroquia La Victoria como herramienta de apoyo para el desarrollo de su economía popular y solidaria. - Calero Sigcha, Jacqueline Celena (2019)
The Technical University of Cotopaxi is currently in a research project whose theme is: "Strengthening of the popular and solidarity economy of the SMEs in the Cotopaxi Province," which seeks to create new business models that encourage the growth of the economy through technological tools. The primary objective of the project is to help to promote and to sell products produced by the Association of Artisans of La Victoria Parish which belongs to Pujilí Canton, that pretends that the crafts are known nationally, and internationally; these products are made handmade, and for this reason, it is feasible to develop a web application that allows promoting handcrafted products that will increase the local economy. This project adopts a model of online store for e-commerce type B2C (Bussiness to Customers) of handmade products known as (potteries), which allows all customers to search, and buy products in various categories for which selection criteria will be used; the adoption of e-commerce results in a web application from which the Association of Artisans of La Victoria Parish will exponentially increase sales. Current software engineering tools, techniques, and models such as (LARAVEL FRAMEWORK 5.7) were used, based on the initial incremental Iterative model for the whole process where the following developed modules are implemented: manage product categories, product detail configuration, manage products, manage news, purchase online, view users, view orders, update profile, register, log in with username and password. Favorable results will be achieved for the 120 members of the association by the creation and use of the web application due to the increase of their sales, and the promotion of their products will improve, on the other hand, the place where they elaborate handicraft products will be known, thus enabling people to visit frequently La Victoria Parish, consequently fulfilling the proposed objective at the beginning of the project.